Cone-Henig Subdifferentials of Set-Valued Maps in Locally Convex Spaces. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In locally convex spaces, the concepts of cone-Henig subgradient and cone-Henig subdifferential for the set-valued mapping are introduced through the linear functionals. The theorems of existence for Henig efficient point and cone-Henig subdifferential are proposed, and the sufficient and necessary condition for a linear functional being a cone-Henig subgradient is established.